A Novel Method of Synthesizing Boron‐doped Carbon Catalysts. Issue 6 (31st October 2018) - Suo, N.; Huang, H.; Wu, A. M.; Cao, G. Z.; Zhang, G. F.
Abstract: Boron‐doped carbon catalysts are prepared by a novel method combining hot filament chemical vapor deposition technique with high temperature annealing treatment. Nano‐boron powders are coated by thin diamond layers and then the coated nano‐boron powders are annealed for different times at 1, 300 °C in vacuum. The morphology, microstructure, and chemical bonding states of the synthetized materials have been investigated by scanning electron microscope (SEM), X‐ray diffraction (XRD), Raman spectroscopy, Fourier transform infrared spectroscopy (FT‐IR), and X‐ray photoelectron spectroscopy (XPS), respectively. The results indicate that boron atoms have diffused into the carbon lattice and the content of doping boron rises gradually with the increase of annealing time. The characteristic signal of the B‐C bond will vanish and of the signal B4 C will appear, if the annealing time is too long. The experimental results of rotating disk electrode (RDE) voltammetry illustrate that the catalyst obtained after annealing for 2 h has the highest electrocatalytic oxygen reduction reaction (ORR) activity. The response current characterized by chronoamperometry exhibits that the deposits with a higher catalytic activity have a poorer stability and methanol tolerance.